Pengaruh Leverage, Profitability, Dan Liquidity Terhadap Company Value Dengan Dividend Policy Sebagai Variabel Mediasi Pada Perusahaan Yang Terdaftar Dalam Index LQ45 Di BEI 2021-2023 - Prasetyo, Diknas; Murdianingsih, Dian; Ningsih, Diah Wuriah; Rahman, Arief (EconBank: Journal of Economics and Banking, 2025)
The purpose of this study was to examine the effect of Leverage, Profitability, and Liquidity on Company Value with Dividend Policy as a mediating variable in companies listed in the LQ45 Index on the IDX 2021-2023. Purposive sampling was used in collecting samples and 57 data were obtained. Data analysis using the SPSS 26 program which includes the classic assumption test, t hypothesis test, linear regression analysis, and sobel test. The company's annual report was used as the main data source. The results showed that Leverage, Profitability, Liquidity, and Dividend Policy partially had a significant effect on Company Value. Dividend Policy can mediate the influence of Leverage, Profitability, and Liquidity on Company Value.